Is ibrutinib-related atrial fibrillation dose dependent? Insights from an individual case level analysis of the World Health Organization pharmacovigilance database - Alexandre, Joachim; Font, Jonaz; Angélique, Da-Silva; Delapierre, Baptiste; Damaj, Gandhi; Plane, Anne‐Flore; Legallois, Damien; Milliez, Paul; Dolladille, Charles; Chrétien, Basile (Leukemia, 2024)
Whether ibrutinib-related atrial fibrillation (IRAF) is a dose-dependent adverse drug reaction (ADR) and whether ibrutinib should be discontinued or dose-reduced in case of IRAF occurrence remains unknown. Using the World Health Organization individual case safety report pharmacovigilance database, VigiBase®, we aimed to determine the association between ibrutinib dosing regimens and IRAF reporting. Ibrutinib daily dose was extracted from IRAF cases from VigiBase® and was divided into 5 ibrutinib dosing regimen (140-280-420-560 and >560 mg/day). Disproportionality analysis was used to evaluate the association between IRAF reporting and ibrutinib daily dose, through logistic regression. Single term deletions produced the ibrutinib daily dose global p-value. Then, a multivariable adjusted reporting odds-ratio with its 95% confidence interval was calculated for each ibrutinib dosing regimen, against the lowest dosing regimen (140 mg/day) as reference. A total of 1162 IRAF cases were identified in VigiBase® (n = 62 for ibrutinib 140 mg/day, 114 for ibrutinib 280 mg/day, 811 for ibrutinib 420 mg/day, 164 for ibrutinib 560 mg/day and 11 for ibrutinib >560 mg/day). After adjustment on several variables of interest, IRAF reporting was not significantly associated with ibrutinib dosing regimen (p = 0.09). Our results from Vigibase® do not support IRAF as a dose-dependent ADR (ClinicalTrial registration number: NCT06224452).